HOW SERVICE QUALITY AND CUSTOMER SATISFACTION CREATE CUSTOMER LOYALTY AT AN INDONESIAN FAMILY KARAOKE COMPANY: An Empirical Study in PT. NAV Bima Pratama (NAV Karaoke Keluarga) Branch at @MX Mall Malang - Alamsyah Previa Beta Putra (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this research is to examine how Service Quality and Customer Satisfaction create Customer Loyalty at Family Karaoke Company. The use of these variables is able to solve the arising problem within PT. NAV Bima Pratama (NAV Karaoke Keluarga) at @MX Mall., Malang branch. The samples in this research are the customers of PT. NAV Bima Pratama (NAV Karaoke Keluarga) at @MX Mall., Malang branch who use karaoke service. The sampling technique is Purposive sampling with 150 respondents. Partial Least Square (PLS) analysis technique is applied to analyze the data and Sobel test is also utilized to examine the relationship of the existing intervening variables in the hypothesis. The results reveal that the Service Quality has significant relationship on Customer Satisfaction, but as direct influence on Customer Loyalty the relationship does not significant. Then, Customer Satisfaction has a significant effect on Customer Loyalty. Finally, in indirect relationship between Service Quality and Customer Loyalty become significant when Customer Satisfaction serve as Mediator.Keywords: Service quality, customer satisfaction, customer loyalty, family karaoke